Potential of geo-neutrino measurements at JUNO *Supported in part by National Natural Science Foundation of China (11405056, 11305193, 11205176, 21504063), National Science Foundation of U.S. (EAR 1067983/1068097), Strategic Priority Research Program of the Chinese Academy of Sciences under Grant No. XDA10010100 and CAS Center for Excellence in Particle Physics (CCEPP). (March 2016) - Han 韩, Ran 然; Li 李, Yu-Feng 玉峰; Zhan 占, Liang 亮; McDonough, William F; Cao 曹, Jun 俊; Ludhova, Livia
Abstract: The flux of geoneutrinos at any point on the Earth is a function of the abundance and distribution of radioactive elements within our planet. This flux has been successfully detected by the 1-kt KamLAND and 0.3-kt Borexino detectors, with these measurements being limited by their low statistics. The planned 20-kt JUNO detector will provide an exciting opportunity to obtain a high statistics measurement, which will provide data to address several questions of geological importance. This paper presents the JUNO detector design concept, the expected geo-neutrino signal and corresponding backgrounds. The precision level of geo-neutrino measurements at JUNO is obtained with the standard least-squares method. The potential of the Th/U ratio and mantle measurements is also discussed.